Photovoltaic System with Smart Tracking of the Optimal Working Point - PATARAU, T.; RUSU, A.; MOGA, D.; PETREUS, D.; MUNTEANU, M. (Advances in Electrical and Computer Engineering, 2010)
A photovoltaic (PV) system, based on a Maximum Power Point Tracking (MPPT) controller that extracts the maximum possible output power from the solar panel is described. Output efficiency of a PV energy system can be achieved only if the system working point is brought near the maximum power point (MPP). The proposed system, making use of several MPPT control algorithms (Perturb and Observe, Incremental conductance, Fuzzy Logic), demonstrates in simulations as well as in real experiments good tracking of the optimal working point.